Variation in leaf wettability traits along a tropical montane elevation gradient. Issue 3 (27th July 2016) - Goldsmith, Gregory R.; Bentley, Lisa Patrick; Shenkin, Alexander; Salinas, Norma; Blonder, Benjamin; Martin, Roberta E.; Castro‐Ccossco, Rosa; Chambi‐Porroa, Percy; Diaz, Sandra; Enquist, Brian J.; Asner, Gregory P.; Malhi, Yadvinder
Summary: Leaf wetting is often considered to have negative effects on plant function, such that wet environments may select for leaves with certain leaf surface, morphological, and architectural traits that reduce leaf wettability. However, there is growing recognition that leaf wetting can have positive effects. We measured variation in two traits, leaf drip tips and leaf water repellency, in a series of nine tropical forest communities occurring along a 3300‐m elevation gradient in southern Peru. To extend this climatic gradient, we also assembled published leaf water repellency values from 17 additional sites. We then tested hypotheses for how these traits should vary as a function of climate. Contrary to expectations, we found that the proportion of species with drip tips did not increase with increasing precipitation. Instead, drip tips increased with increasing temperature. Moreover, leaf water repellency was very low in our sites and the global analysis indicated high repellency only in sites with low precipitation and temperatures. Our findings suggest that drip tips and repellency may not solely reflect the negative effects of wetting on plant function. Understanding the drivers of leaf wettability traits can provide insight into the effects of leaf wetting on plant, community, and ecosystem function. Abstract : See also the Commentary on this article by McDowell & Xu, 214 : 903–904 .